Evolución Presupuestal para Operaciones Militares en el VRAEM y su Influencia en la Seguridad Nacional - Zorrilla Nolasco, Carlos (2024)
The Peruvian State allocates resources to satisfy the requirements of the Armed Forces, allowing them to develop military operations and actions, ensuring coexistence and social peace, reducing threats that threaten national security. The objective of this article is to determine the influence that existed between the budget evolution for military operations in the Valley of the Apurímac, Ene and Mantaro rivers (VRAEM) and National Security. For its formulation, the quantitative approach was used, based on open source statistical results, which allowed us to know how the cross-sectional design research variables influence, based on theory and the description of reality. It is also a correlational study since the results of surveys carried out during the year of the study were used. The product of the inferential analysis was a total of 0.659, which represented a significant influence, and allowed determining the existence of influence between the variables, and these with their dimensions being supported, not only with the application of the instruments, but also, by the provisions of current regulations. It was concluded that there is influence between the VRAEM Budget on the impact on National Security.